Strategi Kebahasaan Presiden Prabowo Dalam Acara Prabowo Menjawab: Analisis Wacana Kritis Model Teun A. Van Dijk - Ahmad Faza As.syaqil Widad; Mukhzamilah (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This study aims to describe the linguistic strategies of President Prabowo Subianto in the Prabowo Menjawab program using Teun A. van Dijk’s Critical Discourse Analysis framework. This research specifically examines three aspects: text structure, social cognition representing ideology, and social context underlying discourse production. The selection of Prabowo Menjawab as the object of study is based on its characteristics as a critical interview format in digital media that displays complex and spontaneous linguistic dynamics. This study uses a descriptive research approach with qualitative methodology. The data source is the video recording of the Prabowo Menjawab program broadcast on the Narasi Newsroom YouTube channel on April 7, 2025. Data was collected through observation and note-taking techniques with stages of in-depth listening, verbatim transcription, and identification and coding based on van Dijk’s analytical dimensions. The data analysis technique uses the interactive model of Miles, Huberman, and Saldana, which includes data condensation, data display, and conclusion drawing. The results show three main findings. First, in the text structure dimension, President Prabowo constructs central themes of economic sovereignty, debt rationalization, democracy management, and anti-corruption efforts. The superstructure follows a consistent justification-argumentation scheme, while the microstructure utilizes semantic strategies (meaning shifts, differentiation), syntactic strategies (inclusive pronouns, conditional sentences), stylistic strategies (confrontational and militaristic diction), and rhetorical strategies (repetition, personification, antithesis). Second, in the social cognition dimension, six interrelated ideological dimensions are identified: economic nationalism, national stability, technocratic legitimacy, justice populism, authoritative leadership, and meritocratic elitism. Third, in the social context dimension, President Prabowo’s discourse represents a strategic effort to build political consensus and affirm leadership authority during the power transition, by utilizing privileged access to digital media.